Psychogenic Nonepileptic Seizures: A Pilot Study of a Brief Educational Intervention. Issue 2 (20th September 2012) - Thompson, Noreen; Connelly, Lynne; Peltzer, Jill; Nowack, William J.; Hamera, Edna; Hunter, Edward E.
<x xml:space="preserve">Abstract</x> Purpose Attending to psychological support and education from the time of diagnosis will assist patients in their acceptance of the need for psychological services. Design and Methods An intervention was provided at the time of diagnosis of psychogenic nonepileptic seizures. This randomized control pilot study examined outcomes 6–8 weeks after discharge from the hospital. Findings All subjects in the treatment group made and/or kept an appointment with a psychotherapist or psychiatrist within 6–8 weeks of discharge from the hospital as compared with 50% of the control group. Practice Implications This supportive approach assists patients to accept the functional or nonorganic nature of their symptoms and the need for psychological services.